Huangqi Guizhi Wuwu Decoction Improves Arthritis and Pathological Damage of Heart and Lung in TNF-Tg Mice - Wang, Yi; Chen, Tao; Yang, Can; Li, Qiang; Ma, Mengjiao; Xu, Hao; Shi, Qi; Wang, Yongjun; Wang, Youhua; Liang, Qianqian (Frontiers in Pharmacology, 2022)
Background: Huangqi Guizhi Wuwu Decoction (HGWD) is a traditional and effective Chinese medicine compound decoction for the treatment of rheumatoid arthritis (RA). However, there is few research on the treatment of rheumatoid cardiopulmonary complications. The present study was to study whether HGWD can alleviate the pathological changes caused by rheumatoid arthritis and cardiopulmonary complications. Methods: Five 3-month-old TNF-Tg mice were treated with HGWD (9.1 g/kg) once a day or the same dose of normal saline lasted for 8 weeks, and wild-type littermates of the same age were used as a negative control, and methotrexate (MTX) was intraperitoneally administered as a positive control. After the treatment, pathological staining was performed on the mouse ankle joints, heart, and lungs. Result: It was found that HGWD reduced the inflammation of the ankle joint synovium in TNF-Tg mice, and reduced myocardial hypertrophy, inflammatory infiltration and fibrosis of heart, as well as lung inflammation and fibrosis. Immunohistochemical staining with anti-TNF-α antibody showed that HGWD reduced the expression of TNF-α in the heart of TNF-Tg mice. Conclusion: In conclusion, HGWD alleviates joint inflammation in TNF-Tg mice and reduces the pathological changes of the heart and lungs.